Sexual dimorphism in upper-limb blood restricted exercise - Borges, Afonso de Sousa Gomes (2018)
Purpose: Low intensity blood flow restricted (LIBFR) exercise elicits acute changes in torque output and muscle activation. The magnitude of these changes affect chronic adaptions to this type of training. However, despite its widespread use by men and women, it is not known whether the acute impact of LIBFR follows a sexually dimorphic pattern. We aimed at exploring whether: 1) the relationship of absolute occlusion pressure (AOP) with arm circumference and resting blood pressure (BP) differs between men and women; and 2) there is sexual dimorphism in fatigue following two different upper-limb resistance-training protocols (non-BFR high intensity - HI resistance training vs. LIBFR exercise). Methods: Sixty-two healthy young participants (31 men: 21.7 ± 2.3; 31 women: 22.0 ± 2.0 yrs) were included in this study. Participants visited the laboratory on two different occasions (biceps curl - HI day vs. LIBFR day; randomized and counterbalanced fashion). Arm circumference as well as other anthropometric measurements were obtained from each participant. BP and AOP were taken twice for reliability purposes. Participants performed maximum voluntary contractions (MVC) at pre- and post-training time points. One-repetition maximum (1RM) was quantified in each participant before pre-training MVC. HI was performed at 75% 1RM and LIBFR at 20% 1RM with 60% blood flow restriction (BFR). Results: Multiple linear regression analyses showed that arm circumference, systolic BP and sex were all significant predictors of AOP (p < 0.05), explaining 42% of its variance. Bland Altman plots revealed that the mean difference between actual and estimated AOP was virtually zero (men: -0.14; women: -0.01 mmHg), with no systematic over or under-estimation. Both HI and LIBFR training protocols induced significant muscle fatigue in men and women from pre- to post-training (p < 0.05). HI was more fatiguing than LIBFR in both sexes (p < 0.05) even after controlling for the differences in volume load between protocols. Importantly, the magnitude of torque decrement was similar between men and women after HI and LIBFR training. Conclusions: Arm circumference, systolic BP and sex are significant predictors of upper-limb AOP. Their measurement allows the indirect estimation of BFR pressure to use within the context of exercise training. Performing upper-limb LIBFR exercise using a multiple-set training protocol is less fatiguing than HI resistance exercise in men and women and this is independent of volume load. Torque decrements in response to upper-limb LIBFR and HI do not follow a sexually dimorphic pattern, providing evidence that there is no need to establish different guidelines for men and women when prescribing upper-limb LIBFR exercise.